2021
DOI: 10.3390/en14248454
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Viscoelastic-Surfactant-Induced Wettability Alteration in Porous Media

Abstract: Wettability alteration is one of the most important mechanisms of surfactant flooding. In this work, the combined Amott/USBM (United States Bureau of Mines) method was applied to study the average wettability alteration of initially neutral cores after viscoelastic-surfactant (VES) filtration. The effects of static aging, dynamic aging, VES concentration, filtration flow rate, and pore radius on the alteration of a core’s average wettability were studied. The wettability-alteration trends measured by Amott and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…VES alone can achieve IFT reduction and mobility control at the same time, which was done previously by combining polymers and surfactants . Apart from the aforementioned advantages, the wettability alteration potential of some VES was proven to be an important contributor to incremental oil recovery …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…VES alone can achieve IFT reduction and mobility control at the same time, which was done previously by combining polymers and surfactants . Apart from the aforementioned advantages, the wettability alteration potential of some VES was proven to be an important contributor to incremental oil recovery …”
Section: Introductionmentioning
confidence: 92%
“…10 Apart from the aforementioned advantages, the wettability alteration potential of some VES was proven to be an important contributor to incremental oil recovery. 11 A major concern in the application of VES is the retention of surfactants. Studies have shown that the retention of VES is considerably impacted by pore radius, VES concentration, displacing velocity, and salinity.…”
Section: Introductionmentioning
confidence: 99%